Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) terhadap Motivasi dan Hasil Belajar IPA Siswa SMP - Nismayanti Lahagu; Amin Otoni Harefa; Desman Telaumbanua (Program Studi Pendidikan Biologi - Universitas Nias, 2023)
The low motivation and learning outcomes of students in mathematics learning require innovative, contextual learning models. This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model on students’ motivation and natural science learning outcomes. An experimental method with a randomized control-group pretest–posttest design was applied to 67 eighth-grade students of SMP Negeri 1 Namohalu Esiwa, who were divided into experimental and control classes. The instruments consisted of essay tests and motivation questionnaires that had been tested for validity and reliability. The results showed that the average learning motivation in the experimental class increased from 66.03 (moderate category) to 80.7 (good category), while learning outcomes increased from 62.83 (moderate) to 85.35 (good). Based on the two-tailed t-test, the calculated t-value was 9.8566 for the motivation variable and 9.2406 for the learning outcomes variable. Both values exceeded the t-table value at the 0.05 significance level, indicating that the null hypothesis was rejected. Thus, the CTL model has a significant effect on improving motivation and mathematics learning outcomes.